2018
DOI: 10.1080/2162402x.2018.1461303
|View full text |Cite|
|
Sign up to set email alerts
|

Th17 cell-derived IL-17A promoted tumor progression via STAT3/NF-κB/Notch1 signaling in non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) accounts for the majority of all lung cancer cases, which is the leading cause of cancer deaths worldwide. IL-17A, the major effector cytokine derived from Th17 cells, is a key cytokine in tumor pathogenesis and modulates tumor progression. We aimed to identify whether IL-17A derived from Th17 cells promotes the progression of NSCLC. Here we found that the level of Th17 cells was increased in NSCLC and IL-17A was mainly produced by CD4 C cells (Th17 cells) in NSCLC. IL-17A en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…On the other hand, the percentages of neutrophils, T follicular helper (Tfh) cells and M0 and M2 macrophages were associated with significantly decreased OS rates [respective HRs of 1.08 ( p < 0.01); 1.07 ( p = 0.01); 1.02 ( p = 0.01) and HR = 1.02 ( p = 0.03)] ( Tamminga et al, 2020 ). Not surprisingly, these findings are consistent with the co-existence of augmentative suppressive interactions between different types of suppressor cells in the TME of NSCLC ( Wang et al, 2018 ; Ferreira et al, 2020 ).…”
Section: Partnering Of Non-small Cell Lung Cancer With Neutrophils Assupporting
confidence: 82%
“…On the other hand, the percentages of neutrophils, T follicular helper (Tfh) cells and M0 and M2 macrophages were associated with significantly decreased OS rates [respective HRs of 1.08 ( p < 0.01); 1.07 ( p = 0.01); 1.02 ( p = 0.01) and HR = 1.02 ( p = 0.03)] ( Tamminga et al, 2020 ). Not surprisingly, these findings are consistent with the co-existence of augmentative suppressive interactions between different types of suppressor cells in the TME of NSCLC ( Wang et al, 2018 ; Ferreira et al, 2020 ).…”
Section: Partnering Of Non-small Cell Lung Cancer With Neutrophils Assupporting
confidence: 82%
“…The intratumoral levels of IL-17 and its receptor are also associated with poorer postresection HCC recurrence and patient survival [ 35 , 37 ]. Apart from HCC, IL-17 has been reported to be involved in other solid cancers such as non-small cell lung cancer [ 38 ] and medulloblastoma [ 39 ], suggesting its broad involvement in oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that IL-17 promoted the progression of non-small cell lung cancer (NSCLC) through the STAT3/NF-κB/Notch 1 signaling pathway. 35 Another study found that some tumors grew faster in IL-17 knockout mice. 36 A clinical report showed that IL-17 was highly expressed in primary liver cancer, and it might be involved in the carcinogenesis of liver cancer.…”
Section: Discussionmentioning
confidence: 99%